Artificial Intelligence (AI) In Hotel Industry and Future Development: an Extensive In-Depth Literature Review and Bibliometric Analysis - R. Manigandan; Dr. Naga Venkata Raghuram (International Journal of Intelligent Systems and Applications in Engineering, 2022)
21st century the digitalization and modernization are taken over all the industry. Artificial Intelligence enhances the performance of industry and make a better experience and smarter the businesses. This study identifies the role and challenges of artificial intelligence in the hotel industry, as depicted in the recent literature review. An in-depth literature review was conducted between 2019-2022 published articles. In this study we focused on 34 articles, critically analyzed and identified through the content analysis including themes “artificial intelligence” and “hotel industry”. The study provides the bibliometric analysis of the author, keywords, journals, and citation analysis. The findings of the study are to provide future developments and challenges of artificial intelligence in the hotel industry. It also provided novel models to the small hotel through using of AI.